The Impact of Explicit Small Group Instruction on the Phonological Awareness Development of At-Risk Pre-Kindergarten Students - Presson, Cathy (My University, 2015)
The purpose of this action research study was to investigate the effects of explicit small group instruction on the phonological awareness development of at-risk pre-kindergarten students. This quasi-experimental pretest-posttest design study included 27 pre-kindergarteners from two classrooms. The intervention group received explicit small group instruction three times a week, while the control group received curriculum-based implicit and incidental phonological awareness instruction. An independent t-test using the mean gain scores from the pre and posttest Early Literacy IGDI Assessment (two-tailed p= 0.00) suggests that the intervention positively impacted phonological awareness development in this population.
Keywords: Pre-kindergarten; At-risk; Phonological awareness; Explicit instruction; Small group instruction